Erectile dysfunction as a common complication of radical prostatectomy - Kotuła, Jacek; Kapler, Marta; Mąsior, Magdalena Natalia; Zinkow, Karolina; Świerczek, Izabella (Quality in Sport, 2024)
Prostate cancer is a widespread disorder among older men cured in most cases by radical prostatectomy. Erectile dysfunction, among other sexual disabilities, following a prostatectomy, plays an important role in the quality of life of these patients. Due to the high prevalence of this problem, the knowledge about health aspects leading to postoperative erectile dysfunction should be extended, enabling better prevention of this disorder. This study aims to assess the risks and benefits of preoperative sexual stimulation in patients undergoing different types of prostatectomy on erectile dysfunction by analysing available data from articles found on several internet archives such as PubMed, Google Scholar or Embase. This research shows that erectile function in patients undergoing radical prostatectomy depends both on protective factors of ED, risk factors of ED preoperatively, active sexual rehabilitation before and after surgery, and finally on the type of procedure itself. Patients benefit from good sexual conditions before the surgery, few risk factors such as obesity or cardiovascular diseases, having undergone one of nerve-sparing techniques and active sexual rehabilitation in the postoperative period.